Peripheral nerve stimulation measures in a composite gradient system. Issue 3 (23rd March 2015) - Goodrich, K. Craig; Hadley, J. Rock; Kim, Seong‐Eun; Kaggie, Joshua D.; Handler, William B.; Chronik, Blaine A.; Bolster, Bradley D.; Parker, Dennis L.
ABSTRACT: Purpose: This work compared peripheral nerve stimulation (PNS) thresholds for the MRI scanner body gradients (BODY), a head/neck insert gradient (INSERT), and the combination of both gradient sets used simultaneously (COMPOSITE).Methods : For BODY, INSERT and COMPOSITE gradients, PNS thresholds were determined by exposing subject volunteers to stepped increases in gradient strength. For COMPOSITE mode, the INSERT was applied at equal (experiment 1) or double (experiment 2) the BODY gradient strength. Results: The locations and thresholds of peripheral nerve stimulation depended on the gradient system configuration, gradient axis, and gradient strength. Stimulation in the body occurred when using the BODY Y ‐gradient axis either singly (110 T/m/s) or in COMPOSITE mode (315 T/m/s experiment 2) and adding the insert gradient had negligible effect on stimulation. Stimulation in the head/sinus area generally occurred when using the INSERT X ‐gradient either singly (213 T/m/s) or in COMPOSITE mode (320 T/m/s) and adding the body gradient had negligible effect on stimulation. In the COMPOSITE mode, both the location of stimulation and the limiting gradient strength matched location and strength of the limiting component gradient. Conclusion: Stimulation, to a first‐order approximation, is independent for the two gradient systems. In COMPOSITE mode, PNS can be dominated by either of the individual gradient components, indicating that the contribution of each component can be increased until the threshold limit of each component gradient is reached. COMPOSITE gradients provide increased gradient performance with PNS thresholds higher than either component gradient system operating alone. © 2015 Wiley Periodicals, Inc. Concepts Magn Reson Part B (Magn Reson Engineering) 44B: 66–74, 2015